History retweeting itself: imperial feminist appropriations of "Bring Back Our Girls". Issue 5 (2nd September 2016) - Maxfield, Mary
Abstract: Racist and imperialist narratives have long underpinned White and "Northern"/"Western" feminists' representations of people of color and of Africans. Through textual analysis, this essay places Bring Back Our Girls—the recent campaign to locate and return 276 abducted Nigerian students—in the context of this troubled history. Within the Global North, both the appropriation and abandonment of Bring Back Our Girls fundamentally relied upon a conceptual framework rooted in imperialist and racist histories. By revealing the imbrication of the international campaign in existing power relations, this project challenges the assertion that digital campaigns are technologically determined or "outside" history.